An Analysis on English Students’ Ability in Translating from English Into Indonesian - Rossa Ito Hutahaean; Ria Angelina Saragih; Ephy Cryday Yanti Gea; Hotnida Theresia Lubis (Journal on Education, 2023)
This research aims to know the students’ ability. The method used in this research is the qualitative method. The result of the study shows that the students’ ability in translating from English into Indonesian generally is Excellent. The important thing in translation that we have to know is the fact that every language has its own system, structure, and rule. Every language has different way in arranging word by word to be phrases, sentences, paragraphs, or essay.